Un manifeste patrimonial pour la gastronomie - Marie-Hélène Bénetière; Isabelle Chave; Julie Faure; Michaël Vottero (In Situ)
If its recognition by UNESCO in 2010 drew international attention to the gastronomic meal of the French people, the food and culinary fact in the stakes of heritage policies in France is older. This issue of In Situ. Revue des patrimoines thus questions in multiple, multidisciplinary and complementary ways the very notion of "gastronomic heritage" and the way in which it has been identified, constituted, studied, conserved, protected, enhanced and transmitted for nearly fifty years now. Heritage specialists, in their daily professional lives, have adapted to the unprecedented growth of applied research in the field of gastronomy. By exploring the relationship between food and heritage and heritage phenomena, heritage sciences have benefited from the renewed involvement of researchers and have made gastronomy a subject of total study, which can no longer exclude the scope of studies and research carried out by heritage services professionals themselves. From objects to monuments, gastronomy, in its heritage sense, is linked to a wide range of specialized spaces: gardens, vegetable gardens and orchards, conservatories of food and horticultural plants, restaurants, cafés, food production plants, shops selling food products, kitchens, dining rooms, party rooms, collective catering places..., the typology of the places associated, in various ways, with the concept is one of the most rich. In their respective specialities, heritage actors have gradually cleared the field of culinary practices, through the establishment and enhancement of heritage gardens and food plant conservatories, studies of the gastronomic heritage conducted by the services of the General Inventory of Cultural Heritage, work to restore or rehabilitate the architectural framework of gastronomy, protection of historic monuments, monuments and movable objects related to the culinary arts, the collection of specialised funds, sometimes called "gourmet funds", by archives and libraries and the constitution of collections of objects by museums, in particular ecomuseums and social museums. The intangible cultural heritage, which highlights the practices, knowledge and skills of the holders of living traditions, is the most recent heritage development of the culinary field. Thus, well before the inclusion of the French gourmet meal by UNESCO, and even as early as the 1960s, depending on the sector, heritage professionals focused on the field of all material aspects of food and culinary culture: this interest in the infinite variety of material elements of food and culinary culture developed in France, through so many decisive steps to identify, study, preserve and enhance this heritage, sometimes built, sometimes movable, sometimes written, sometimes anthropological. Observation over time and synoptic consideration of the main institutional sectors, as proposed in this issue of In Situ. Revue des patrimoines, give coherence to this approach to the field of gastronomy through tangible and intangible heritage, i.e., at the national, regional or local level, through inventories, legal protection, collection of archives and works of art or scientific, didactic and educational projects.